Design of Fixed Wing Unmanned Aerial Vehicle based on Magnificent Frigatebird - Thakur, Sarvesh; Kumar Gupta, Vijay; Sharma, Abhishek; Singh, Dharmendra (International Journal of Engineering and Technology, 2018)
The Magnificent Frigate Bird has been investigated extensively in the past because of its extraordinary flying capabilities. In this technical paper an effort has made to present a model of a soaring UAV (Unmanned Aerial Vehicle) based on the bird and we end the process by validating our model through CFD analysis of the model on ANSYS FLUENT. Solid-works 2016 was used to model the UAV, Wingspan of the UAV was kept 2.39 m with an Aspect Ratio of 11.6 and fuselage of 1.1m having comfortable cavity for avionics. (Navier Stokes equation) and Energy equation is used to analyze mathematical model of UAV, It is important to note that embracing the nature is how we should proceed even in scientific ways.Â Â